RiceAdvice-WeedManager android application for Sub-Saharan Africa - CGIAR Research Program on Rice (2021)
RiceAdvice-WeedManager was tested in 45 farmers' fields in Senegal. Results showed rice yield increase by 2 t/ha (41%) compared to farmers' practices.